2007
DOI: 10.1021/jo062526t
|View full text |Cite
|
Sign up to set email alerts
|

Enthalpy (ΔH) and Entropy (ΔS) for π-Stacking Interactions in Near-Sandwich Configurations:  Relative Importance of Electrostatic, Dispersive, and Charge-Transfer Effects

Abstract: Interactions between two aromatic rings with various substituents in a near-sandwich configuration have been quantitatively studied using the triptycene derived molecular models. This model system allows a stacking arrangement of two arenes to assume a near perfect face-to-face configuration in its ground state conformation. Comparing to our previous study of the parallel displaced configuration, repulsive interactions are predominant for most arenes currently studied. However, if one arene is strongly electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
35
0
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 28 publications
6
35
0
2
Order By: Relevance
“…From the literature, certain experimental findings were taken into account to improve the final pharmacophore models: planar sandwich or face-to-face parallel-stacked geometry under an attractive charge-transfer interaction between aromatic systems showing electrondeficiency and electron-rich areas, with an energy gain of 1.5 kcal/mol at a distance between ring centers 5 nm. 69 Similar observations were made by Gung et al 70 : ∆H of −2 kcal/mol and a ∆S of −3 kcal/mol. Especially, π-stacking with edgeto-face (T-shaped), also OH-π arrangements, cation-π interactions, and Coulombic enzyme-substrate interactions are reported by Meyer et al 71 An empirical study observed that the aromatic side chains of amino acids prefer an offcentered parallel alignment in proteins (parallel displaced π-stacking).…”
Section: Methodssupporting
confidence: 76%
“…From the literature, certain experimental findings were taken into account to improve the final pharmacophore models: planar sandwich or face-to-face parallel-stacked geometry under an attractive charge-transfer interaction between aromatic systems showing electrondeficiency and electron-rich areas, with an energy gain of 1.5 kcal/mol at a distance between ring centers 5 nm. 69 Similar observations were made by Gung et al 70 : ∆H of −2 kcal/mol and a ∆S of −3 kcal/mol. Especially, π-stacking with edgeto-face (T-shaped), also OH-π arrangements, cation-π interactions, and Coulombic enzyme-substrate interactions are reported by Meyer et al 71 An empirical study observed that the aromatic side chains of amino acids prefer an offcentered parallel alignment in proteins (parallel displaced π-stacking).…”
Section: Methodssupporting
confidence: 76%
“…Similar findings have also been reported by Kim et al 16 Ringer, Sinnokrot, Lively, and Sherrill18 further demonstrated the additivity of substituent effects in multiply-substituted benzene heterodimers. Additivity in the case of fluorine substitution has also been shown experimentally by Gung and co-workers 36. Such strict additivity is contrary to expectations if π-polarization were the dominant cause of substituent effects, because the incremental polarization of the aryl π-system should decrease with each additional substituent.…”
Section: Introductionmentioning
confidence: 73%
“…[266] In contrast to non-or minimally fluorinated aromatic compounds, which crystallize preferentially in a Vshaped arrangement, the electrostatic interaction between unsubstituted and highly fluorinated aromatic compounds results largely in a face-to-face stacking. [269] Compounds with highly electron-deficient rings (for example, with pentafluorobenzoate) exhibited consistently higher attractive forces regardless of the nature of the other aryl residue. [269] Compounds with highly electron-deficient rings (for example, with pentafluorobenzoate) exhibited consistently higher attractive forces regardless of the nature of the other aryl residue.…”
Section: Interactions Between Electronically Neutral Polar Groupsmentioning
confidence: 99%